Patient adherence and factors associated with short-term oral antibiotic use for acute respiratory infections (ISPA) in Wedi primary health care - Putri, Aristhasari; Septyasari, Avanilla Fany; Ridhwan, Adib Muhammad (Borobudur Pharmacy Review, 2025)
Upper respiratory tract infection (URTI) is a common illness in Indonesia caused by microorganisms, caused by microorganisms that affect the upper respiratory tract. Short-term antibiotic therapy is frequently prescribed, but many patients do not adhere to this treatment. Non-compliance often occurs because patients feel better, forget to take their medication, or do not follow the prescribed regimen properly. This can lead to poor clinical outcomes and an increased risk of bacterial resistance. This study was conducted to to assess the level of adherence and contributing factor among URTI patients to short-term oral antibiotic therapy. A cross-sectional research design was employed, utilizing a structured questionnaire for data collection. The sampling method applied was purposive sampling, which included a cohort of 31 patients with URTI who were prescribed short term antibiotics. The results showed that 77.4% of respondents were compliant, while 22.6% were non-compliant. Factors that significantly associated with adherence included educational level and occupation (p < 0.05), while age did not show a significant relationship (p > 0.05). Another factors influencing non-adherence included inadequate information provided by healthcare professionals, busy schedules, premature discontinuation of therapy due to perceived recovery, lack of family support, and difficulty swallowing medication. Pharmacists can play a significant role in improving compliance by providing clear information and utilizing reminder tools to assist patients in taking their medication as prescribed.